THE INTERNATIONAL ACTIVITY OF THE UKRAINIAN BOOK PUBLISHING INDUSTRY - Olena Karakoz (Культура і мистецтво у сучасному світі, 2020)
The purpose of this article is to analyse the programmes of the international cooperation in the book publishing industry and to identify promising directions in the development of the Ukrainian book industry in the process of such cooperation. The research methodology is based on the use of comparative and historical, statistical methods that have provided comprehensive information in the field of international cooperation of Ukrainian publishing as of an activity that is very important for the cultural and intellectual development of the society. Bibliographic methods – functional, analytical and thematic, structural and typological – helped to determine the forms and methods to expand cooperation in the field of book publishing and at the same time define development prospects of the domestic book publishing, distribution and usage. The scientific novelty lies in the fact that current international communication programmes in the field of publishing industry have been comprehensively examined for the first time. The field of international cooperation in the book publishing industry has been analysed as a complex systematic entity that performs its functions in various aspects and at different levels. Therefore, book publishing as a means of dissemination of national culture is at the same time a determining factor of progress of the world book industry and a phenomenon of international culture. An international interaction of cultures is needed for the development of each individual national culture, for the emergence of new resources and motivation for improvement. Thus, the necessity of international book publishing contacts depends on the objective needs. Conclusions. It is shown that the international cooperation in the field of book publishing is aimed at the enhancing of the international cooperation of Ukraine with other countries; contributes to the strengthening of the international image of Ukraine; serves as a statement of common to all values; promotes the development of the national book industry; attracts Ukrainians to the world’s spiritual and social values, technological achievements; ensures a direct and proper exchange of cultural, intellectual and material values. The study identifies the main directions of international cooperation, including Ukraine’s participation in the international book fairs, exhibitions; publishers’ participation in the international programmes; intense activity in the field of literature translation, etc. Thus, the strategic goal and priorities of the international cooperation of Ukraine in book publishing industry has been defined: firstly, to increase the level of the national book publishing; secondly, the use of world achievements in domestic practice; thirdly, the promotion of the Ukrainian book publishing in the world.